Zinc Oxide Nanoparticles (ZnONPs) Photocatalyst using Pulse Laser Ablation Method for Antibacterial in Water Polluted - Fatkhiyatus Saadah; Rizka Zakiyatul Miskiyah; Ali Khumaeni (Diponegoro University Semarang Indonesia, 2020)
Synthesis of zinc oxide nanoparticles by pulse laser ablation method has been successed carried out. Synthesis was carried out in aquades medium with a repetition rate variation of 5 Hz, 10 Hz and 15 Hz pulse laser yielding brown colloids. The higher laser repetition rate, the colloidal color will be more dark brown. Characterization of zinc oxide nanoparticles includes UV-Vis, SEM-EDX, FTIR and XRD. The image of SEM shows that zinc oxide nanoparticles have a round shape. Measurement of particle distribution with imageJ software from SEM images showed that ZnO nanoparticles were 23.63 nm, 12.13 nm and 5.59 nm for 5 Hz, 10 Hz and 15 Hz shots. The EDX spectrum analysis results show that only Zn and O atoms in the ZnO nanoparticles colloid are synthesized. FTIR results showed that sprocket ZnO was formed at wave number 457 cm-1 and 545 cm-1. The XRD analysis results also show some peaks known as the ZnO phase. This indicates that ZnO nanoparticles have been formed. The testing of the antibacterial activity of ZnO nanoparticles using a liquid dilution method with nanoparticle concentrations of 40 ppm, 60 ppm and 80 ppm. The test results showed the percentage of degradation of Escherichia coli bacteria at concentrations of 40 ppm, 60 ppm and 80 ppm respectively at 89.60%, 97.76% and 98, 70%.